A flash of polarized optical light points to an aspherical 'cow'. Issue 3 (21st February 2023) - Maund, Justyn R; Höflich, Peter A; Steele, Iain A; Yang(杨轶), Yi; Wiersema, Klaas; Kobayashi, Shiho; Jordana-Mitjans, Nuria; Mundell, Carole; Gomboc, Andreja; Guidorzi, Cristiano; Smith, Robert J
ABSTRACT: The astronomical transient AT2018cow is the closest example of the new class of luminous, fast blue optical transients (FBOTs). Liverpool telescope RINGO3 observations of AT 2018cow are reported here, which constitute the earliest polarimetric observations of an FBOT. At $5.7\, days$ post-explosion, the optical emission of AT2018cow exhibited a chromatic polarization spike that reached $\sim 7{{\ \rm per\ cent}}$ at red wavelengths. This is the highest intrinsic polarization recorded for a non-relativistic explosive transient and is observed in multiple bands and at multiple epochs over the first night of observations, before rapidly declining. The apparent wavelength dependence of the polarization may arise through depolarization or dilution of the polarized flux, due to conditions in AT 2018cow at early times. A second 'bump' in the polarization is observed at blue wavelengths at $\sim 12\, days$ . Such a high polarization requires an extremely aspherical geometry that is only apparent for a brief period (<1 d), such as shock breakout through an optically thick disk. For a disk-like configuration, the ratio of the thickness to radial extent must be $\sim 10{{\ \rm per\ cent}}$ .